Outstretched Index Finger - A Pointer is Peculiar Behaviour Characteristic of Angelman Syndrome in Adults – A Case Series Study - Martin, Peter (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Objective: To describe a behavioural feature, the outstretched pointing (and shaking) index finger, as a clue to the clinical diagnosis of Angelman syndrome (AS) in adults. Methods: A case series, consisting of 43 adult individuals with the clinical diagnosis of AS, approved by genetic testing is presented. In 16/43 patients the clinical diagnosis was made by the author, mostly due to behavioural signs, including the pointing gesture, which he had increasingly noticed as a behavioural key feature in his adult patients with AS. Conclusion: Pointing with the outstretched index finger is a communicative gesture frequently seen in adult persons with AS. Its absence is most likely due to more limited motor and/or intellectual functions, in phenotypes caused by deletions of 15q11-13 respectively. It can be seen as a clinical sign that significantly contributes to the diagnosis in adulthood.